2007
DOI: 10.1111/j.1399-0039.2007.00878.x
|View full text |Cite
|
Sign up to set email alerts
|

HLA‐associated genetic resistance and susceptibility to type I diabetes in French North Africans and French natives

Abstract: The distribution of human leukocyte antigen (HLA)-DRB1-DQA1-DQB1 haplotypes was analyzed separately in two distinct French ethnic groups with type I diabetes (T1D), i.e. French North African migrants (n= 64, mean age at diagnosis = 8.25 years) and ancient French natives (n= 60, mean age at diagnosis = 7.42 years). HLA associations were determined by calculating odds ratios (ORs) between patients and two ethnic-matched control populations. Results show highly similar ORs for the conservative DRB1*0301-DQA1*0501… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
14
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 25 publications
5
14
1
Order By: Relevance
“…Among our samples, DQA1*05:05 allele is in strong linkage with DQB1*03:01 (Table ), a protective allele (Table ) that codes for an Aspartic acid in the position 57 (Asp57), a feature highly associated with T1D protection (Table ). Also, variation in the protective effect of DQA1*05:05‐DQB1*03:01 has been referred to depend on DRB1 contribution, suggesting it could be a consequence of a Valine at codon 86 (Guérin et al., ). However, in the present study, a Valine in DRB1 position 86 associated to DQA1*05:05 does not reveal a significant protection effect (OR = 0.58, p = .46), even when considering the total sample (OR = 0.91, p = .61), but this lack of significance could be just a consequence of the small sample size.…”
Section: Resultsmentioning
confidence: 99%
“…Among our samples, DQA1*05:05 allele is in strong linkage with DQB1*03:01 (Table ), a protective allele (Table ) that codes for an Aspartic acid in the position 57 (Asp57), a feature highly associated with T1D protection (Table ). Also, variation in the protective effect of DQA1*05:05‐DQB1*03:01 has been referred to depend on DRB1 contribution, suggesting it could be a consequence of a Valine at codon 86 (Guérin et al., ). However, in the present study, a Valine in DRB1 position 86 associated to DQA1*05:05 does not reveal a significant protection effect (OR = 0.58, p = .46), even when considering the total sample (OR = 0.91, p = .61), but this lack of significance could be just a consequence of the small sample size.…”
Section: Resultsmentioning
confidence: 99%
“…The incidence of T1DM is rapidly increasing in specific regions and shows a trend toward earlier age of onset and also it is highly variable among different ethnic groups (6,7,8,9,10,11,12,13,14,15). It is predicted that the overall incidence of T1DM is about 40% higher in recent years as compared to its incidence in 1997 (16).…”
Section: Discussionmentioning
confidence: 99%
“…T1DM is an autoimmune disorder and the risk for the disease is increased by specific HLA DR/DQ alleles [e.g., DRB1*03-DQB1*0201 (DR3) or DRB1*04-DQB1*0302 (DR4)] (2,3,4,5). Trends in the frequency of HLA DR-DQ haplotypes showed different associations in distinct ethnic groups (6,7,8,9,10,11,12,13,14,15) and also in the same region (11). With these variations in mind, T1DM patients and healthy controls from the population of the Southeast Region of Turkey were investigated for HLA DR-DQ haplotypes.…”
Section: Introductionmentioning
confidence: 97%
“…In addition, DQ2 (DQB1*0201-DQA1*0501) and DQ8 (DQB1*0302-DQA1*0301), which occur in strong linkage disequilibrium with DR3 and DR4, respectively, are strongly associated with the disease in several Caucasian populations, especially when present in the DR3/DR4 heterozygous condition [78][79][80][81][82][83]. It has been suggested that DR3/DR4 heterozygosity exerts a synergistic effect and provides a much greater risk to T1D than DR3 homozygosity in most populations.…”
Section: Mhcmentioning
confidence: 97%
“…Worldwide, T1D has been reported to be strongly associated with HLA-DR3 or -DR4, or both alleles, whereas HLA-DR15 has been found to be protective in north Indians and several other populations [73][74][75][76][77][78][79][80][81][82]. In addition, DQ2 (DQB1*0201-DQA1*0501) and DQ8 (DQB1*0302-DQA1*0301), which occur in strong linkage disequilibrium with DR3 and DR4, respectively, are strongly associated with the disease in several Caucasian populations, especially when present in the DR3/DR4 heterozygous condition [78][79][80][81][82][83].…”
Section: Mhcmentioning
confidence: 99%